Two Notable Sculptural-Spatial Memorials in the Topography of Priština Commemorating the Victims of World War II - Vukotić Lazar, Marta M.; Marković Savić, Olivera S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper deals with Yugoslavia in the aftermath of World War II, a time when the preservation of revolutionary tradition and the legacy of the People’s Liberation Struggle were elevated to the status of a paramount social imperative. Cultural policy during this era functioned as a heterogeneous and far-reaching system of systematically coordinated actions, extending across both the spiritual and material domains of cultural life—entirely subordinated to the directives of political leadership. Within this framework, state authorities promptly embraced public sculpture as a vital medium for the effective transmission of ideological values and for advancing a broader ideological project: the symbolic reconfiguration of the cultural and political landscape of the New Yugoslavia. This study centers on two sculptural-spatial WWII memorials in Priština, the capital of the autonomous province of Kosovo and Metohija, in order to illuminate their significance within both artistic and commemorative contexts. The first is the Monument to the People’s Liberation Struggle of the People of Kosovo and Metohija (1959–1961) by sculptor Miodrag Živković, located in the central square of the “new city center” constructed after the war. The second is the Memorial Cemetery for Fallen Fighters (1960–1961), situated on Matičane Hill in the Velania neighborhood overlooking the city, designed by architect Svetislav Ličina in collaboration with architect Prvoslav Janković. Through the lens of sculptural architectonics and urban memory, the study seeks to underscore the cultural, symbolic, and spatial import of these two significant achievements—situating them not only within the individual artistic trajectories of their respective creators, but also within the broader evolution of post-WWII monumental art in Serbia. These works, produced by artists whose distinctive creative vocabularies transcended the strictures of ideological orthodoxy, are examined as both critical contributions to their respective oeuvres and as emblematic “sites of memory” embedded in the urban fabric of Priština. In this dual capacity, they are essential to understanding the complex commemorative cartography of the former Yugoslavia as it took shape in the ideological and spatial aftermath of the liberation at the end of WWII.